Tingkat Kebutuhan Ruang Terbuka Hijau - Fitri, Alfita; Invanni, Ichsan; Arfan, Amal (UNIVERSITAS NEGERI MAKASSAR, 2020)
This research was conducted in Polewali District Polewali Mandar Regency. This study aims to determine the availability of green open space in 2018 in Polewali District Polewali Mandar Regency and calculate the need for open green space in 2018 by area, population and green open space projected needs for 2028. This type of research is quantitative descriptive. This study uses the application's help Geographic Information System (GIS), groundcheck field and observation. The results of this study indicate the need of green open space in Polewali District Polewali Mandar Regency to meet the standard of 30% by area of 788.1 Ha should be available, but the green open space available in 2018 only 500.67 Ha or 19% of the area with details 383, 49 Ha or 15% of public green open space and 117.18 Ha or 4% private green open space. The results of calculation of green open space needs based on population in 2018 amounted to 123.8 Ha. The projection of green open space needs in 2028 amounted to 138.8 Ha. Green open space needs in 2018 based on an area not yet fulfilled, while based on population needs were already met by a ratio of 1/5 between the need for open green space with availability of green open space in Polewali District Polewali Mandar Regency.